A description and summary of the Antarctic Humpback Whale Catalogue - Allen, Judith; Carlson, Carole; Stevick, Peter T. (J. Cetacean Res. Manage., 2020)
The Antarctic Humpback Whale Catalogue (AHWC) is an international collaborative project investigating movement patterns of humpback whales in the Southern Ocean and corresponding lower latitude waters. The collection contains records contributed by 261 researchers and opportunistic sources. Photographs come from all of the Antarctic management areas, the feeding grounds in southern Chile and also most of the known or suspected low-latitude breeding areas and span more than two decades. This allows comparisons to be made over all of the major regions used by Southern Hemisphere humpback whales. The fluke, left dorsal fin/flank and right dorsal fin/flank collections represent 3,655, 413 and 407 individual whales respectively. There were 194 individuals resighted in more than one year, and 82 individuals resighted in more than one region. Resightings document movement along the western coast of South America and movement between the Antarctic Peninsula and western coast of South America and Central America. A single individual from Brazil was resighted off South Georgia, representing the first documented link between the Brazilian breeding ground and any feeding area. A second individual from Brazil was resighted off Madagascar, documenting long distance movement of a female between non-adjacent breeding areas. Resightings also include two matches between American Samoa and the Antarctic Peninsula, documenting the first known feeding site for American Somoa and setting a new long distance seasonal migration record. Three matches between Sector V and eastern Australia support earlier evidence provided by Discovery tags. Multiple resightings of individuals in the Antarctic Peninsula during more than one season indicate that humpback whales in this area show some degree of regional feeding area fidelity. The AHWC provides a powerful non-lethal and non-invasive tool for investigating the movements and population structure of the whales utilising the Southern Ocean Sanctuary. Through this methodical, coordinated comparison and maintenance of collections from across the hemisphere, large-scale movement patterns may be examined, both within the Antarctic, and from the Antarctic to breeding grounds at low latitudes.